A Deep Analysis of the Chinese Hukou System Facts, Impacts, and Reform Paths - Song, Yang. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book explores China's hukou system, by which individuals are registered in a specific geographic region, and the prospects for reform. The history of the hukou system and its instrumental role in Chinese urbanization and labor markets is explained, and readers get a sense of what issues are prioritized by Chinese policymakers as they contemplate reform or change to this system, from hukou- based labor market discrimination, inequality of opportunity, multi-dimensional poverty of rural migrants, the public health consequences of non-hukou migration, and old age insurance for migrants without hukous. The author concludes with a stirring and practical call for hukou reform, articulating a cost-benefit model and providing an array of policy suggestions. This book will interest scholars of Chinese society, demographics and future urbanization. Yang Song is currently a Professor and Assistant Dean of School of Economics at Renmin University of China; he obtained a Ph.D degree in Economics from the Department of Economics at Cornell University in 2013. His research interest mainly lies in labor and development economics with a focus on income distribution and labor market issues in China.
Part I Brief Introduction to China's Hukou System -- Chapter 1: Introduction -- Chapter 2: Current Situation of China's Hukou System -- Part II Comprehensive Impact of the Hukou System -- Chapter 3: Labour Market Discriminations Induced by the Hukou System -- Chapter 4: Unequal Opportunities Induced by the Hukou System -- Chapter 5: The Hukou System and Migrant Workers' Multidimensional Poverty -- Chapter 6: Health Impact of the Hukou System on Migrant Workers -- Chapter 7: Impact of the Hukou System on Old-age Care for Migrant Workers -- Part III Hukou System Reform Path Analysis -- Chapter 8: Significance, Current Situation and Difficulties of Hukou System Reform -- Chapter 9: Is Hukou System Reform Cost-effective -- A Simulation Analysis Based on the Labour Market Model -- Chapter 10: Policy Analysis of Hukou System Linkage Reform -- Chapter 11: Policy Recommendations for Hukou System Reform. .
Keywords: Demography; Population; Population -- Economic aspects; Law and the social sciences; Population and Demography; Population Economics; Socio-Legal Studies